(untitled) (Panacea Journal of Medical Sciences, 2022)
Amblyopia is the leading cause of preventable blindness in children and young. The prevalence of amblyopia in childhood varies between 1-5%, although these values may differ. Most of the visual impairment in amblyopia is reversible if treated early at appropriate time. Various treatment modalities in children include: refractive correction, patching, atropine penalization, binocular therapy, liquid crystal display eyeglasses and transcranial magnetic stimulation. Motive of this article is to give an emphasis on newer management strategy and newer trends in amblyopia therapy. A thorough search of literature was done in PubMed, Scopus, Embase and reference list of articles until December 15, 2020 containing “amblyopia treatment or therapy” was retrieved.